CREATION OF A HEALTHY WORKPLACE ENVIRONMENT TO MOTIVATE EMPLOYEES - Siddu.Sirisha; Palakeeti Kiran; K. Uma Maheswara Rao; Dr.Sk.Shamshad Ahamed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
A positive work environment helps your association since it might bring about expanded income. Each working environment has an exceptional blend of characters, so what motivates one worker may not be guaranteed to rouse others. Find whether an involved methodology or more freedom will help your representatives by getting to know them. An ideal working environment prompts worker work joy, as per this examination paper. The review impacts how well firms capability in the future by underscoring work environment culture inside their undertakings to support representative commitment and inspiration. I involved a poll instrument to quantify the answers in this venture's populace of 150 representatives utilizing the basic irregular testing technique. This will empower their labor force to achieve